The U.S. banking competition and the effects of policy: evidence from U.S. banking over 2011-2017 - Ouyang, Huijie (2018)
This paper aims to examine the competitive condition in the U.S. banking sector as well as how would regulatory and competition policies affect U.S. banking competition after the 2007-2008 global financial crisis. This study adopts the Panzar- Rosse model, including a panel data set from 408 U.S. banks during the post-crisis period from 2011 to 2017, which is applied to conduct the empirical research. According to the literature and empirical result, it is found that the U.S. banking market is in monopolistic competition, and the trend of the competitive condition is rather stable. After the sub-prime crisis, the U.S. bank regulatory and competition policies changed following the evolution of the current banking sector, avoiding repeating the failure of TBTF policies, increasing the stringency of capital regulations and improving the degree of both private and public supervision.